2015
DOI: 10.1089/ars.2014.5901
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Cytoprotective Actions of Hydrogen Sulfide: Translation to Therapeutics

Abstract: A better understanding of the physiological and pathophysiological roles of H2S continues to be restrained by the lack of simple, reliable methods for measurement of H2S synthesis, and the paucity of highly selective inhibitors of enzymes that participate in endogenous H2S synthesis. On the other hand, H2S donors show promise as therapeutics for several important indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 107 publications
(118 reference statements)
2
100
1
Order By: Relevance
“…Rats and mice were provided one of two diets (Harlan Teklad) for 6 wk. One diet ("B-Def") lacked vitamins B 6 , B 9 , and B 12 (49). The control diet was identical except that it contained the abovementioned vitamins and folate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats and mice were provided one of two diets (Harlan Teklad) for 6 wk. One diet ("B-Def") lacked vitamins B 6 , B 9 , and B 12 (49). The control diet was identical except that it contained the abovementioned vitamins and folate.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, hydrogen sulfide (H 2 S) has become recognized as an important signaling molecule in many organs and tissues (8), and particularly as an anti-inflammatory and cytoprotective mediator (9). H 2 S is produced throughout the gastrointestinal (GI) tract, and its synthesis is markedly increased following mucosal injury (10-13).…”
mentioning
confidence: 99%
“…H 2 S is a novel gasotransmitter that has been shown to exert an important role in regulating vascular tone [13]. There is a rapidly expanding body of evidence for important roles of H 2 S in protecting against tissue injury, reducing inflammation, and promoting repair [14]. In animal studies, H 2 S has been shown to play a role in both promoting and inhibiting inflammation and appears to increase survival in animal model of sepsis and shock [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not affect the survival of normal human cells. Several recent studies have shown that H 2 S-releasing NSAIDs, which were initially developed by Wallace et al as anti-inflammatory drugs having no side effects on the gastrointestinal tract, exhibit enhanced chemopreventive effects in cancer cells (7). These compounds inhibit cancer cell proliferation and promote apoptosis, as well as cell cycle arrest.…”
mentioning
confidence: 99%
“…The effects of H 2 S and related compounds on various types of cancers and their ability to suppress cancer development have been described previously (6,7). According to Szabo and colleagues, the production of H 2 S by CBS is increased in colorectal and ovarian cancers and both play an important role in promoting cellular bioenergetics, proliferation, and migration (1).…”
mentioning
confidence: 99%